2010
DOI: 10.1016/j.expneurol.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of guanosine and MK-801 in a quinolinic acid-induced seizure model

Abstract: Quinolinic acid (QA) is an N-methyl-D-aspartate receptor agonist that also promotes glutamate release and inhibits glutamate uptake by astrocytes. QA is used in experimental models of seizures studying the effects of overstimulation of the glutamatergic system. The guanine-based purines (GBPs), including the nucleoside guanosine, have been shown to modulate the glutamatergic system when administered extracellularly. GBPs were shown to inhibit the binding of glutamate and analogs, to be neuroprotective under ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The increase in this electrophysiological pattern is associated with the occurrence of psychotic symptoms and cognitive impairments, which are commonly induced by NMDAR antagonists such as MK-801 and ketamine [123][124][125][126]. Therefore, these results suggest that guanosine might be associated with less side effects when compared with classic NMDAR antagonists [122]. In fact, guanosine is able to prevent the locomotor stimulation induced by MK-801, but not amphetamine-or caffeine-induced hyperlocomotion, reinforcing the notion that this molecule may be a safer modulator of glutamatergic activity [127].…”
Section: Anticonvulsant Effects Of Guanosinementioning
confidence: 85%
See 1 more Smart Citation
“…The increase in this electrophysiological pattern is associated with the occurrence of psychotic symptoms and cognitive impairments, which are commonly induced by NMDAR antagonists such as MK-801 and ketamine [123][124][125][126]. Therefore, these results suggest that guanosine might be associated with less side effects when compared with classic NMDAR antagonists [122]. In fact, guanosine is able to prevent the locomotor stimulation induced by MK-801, but not amphetamine-or caffeine-induced hyperlocomotion, reinforcing the notion that this molecule may be a safer modulator of glutamatergic activity [127].…”
Section: Anticonvulsant Effects Of Guanosinementioning
confidence: 85%
“…This observation supports the idea that the mechanism of glutamatergic modulation elicited by guanosine differs from the mechanisms of classic glutamatergic antagonists. In addition, guanosine was also able to prevent the increase in gamma oscillations induced by QA [122]. The increase in this electrophysiological pattern is associated with the occurrence of psychotic symptoms and cognitive impairments, which are commonly induced by NMDAR antagonists such as MK-801 and ketamine [123][124][125][126].…”
Section: Anticonvulsant Effects Of Guanosinementioning
confidence: 92%
“…In addition to clear EEG changes occurring during the seizure events, we found that quinolinic acid disrupted a prominent basal theta (4-10 Hz) activity during peri-ictal periods and promoted a relative increase in the power level at the gamma band; guanosine, when successfully preventing seizures, counteracted this effect following quinolinic acid administration. Interestingly, we observed that MK-801, a known NMDA-antagonist used as a positive control, presented different spectral effects when compared to guanosine in rats protected against quinolinic acid-induced seizures, producing large gamma oscillations following quinolinic acid administration [67]. Additionally, the combined pre-treatment with both guanosine and MK-801 in this model led to qualitatively different results than the observed when each drug was administered alone [67].…”
Section: Effects Of Guanine-based Purines Against Seizures and Toxicimentioning
confidence: 70%
“…Interestingly, we observed that MK-801, a known NMDA-antagonist used as a positive control, presented different spectral effects when compared to guanosine in rats protected against quinolinic acid-induced seizures, producing large gamma oscillations following quinolinic acid administration [67]. Additionally, the combined pre-treatment with both guanosine and MK-801 in this model led to qualitatively different results than the observed when each drug was administered alone [67]. Considering these recent evidences, we suggest that a diverse mechanism of action between both drugs (guanosine versus MK-801 or perhaps other NMDA antagonists) exists and that guanosine might be related to a lower incidence of cognitive side effects than NMDA antagonists in the clinical setting.…”
Section: Effects Of Guanine-based Purines Against Seizures and Toxicimentioning
confidence: 87%
See 1 more Smart Citation